Case report: When infection lurks behind malignancy: a unique case of primary bone lymphoma mimicking infectious process in the spine - Jaafari, Ayoub; Rizzo, Ornella; Mansour, Sohaïb; Chbabou, Anas; Trepant, Anne-Laure; Attou, Rachid; Mathey, Celine (Frontiers in Nuclear Medicine, 2024)
Primary bone lymphoma of the spine (PBL) is a rare entity that may be misdiagnosed due to its atypical location and clinical and imaging features mimicking certain pathologies as infectious processes, which complicates and delays diagnosis. Our case reports a patient in her sixties who had been suffering from chronic low back pain for a year, and had gradually started to develop cruralgia. She underwent a blood sample, magnetic resonance imaging (MRI), and positron emission tomography (18F-FDG-PET/CT) which revealed inflammatory syndrome, and an image of spondylodiscitis of the lumbar spine associated with a morphological and metabolical widespread invasion posteriorly suggesting epiduritis. No other lesions were found on the rest of the body. Neurosurgical management was performed and a biopsy was made. Histological results showed aggressive and diffuse large B-cell lymphoma, suggesting a diagnosis of PBL. This case highlights the first case of spondylodiscitis mimicking PBL in the lumbar spine, the intricacies of the diagnostic work-up, and the complexity of discriminating with an infectious process in the spine, as both have a similar, non-specific clinical presentation, while morphological and metabolic findings can be alike.